A circle of elephants - Dinerstein, Eric, 1952- (Disney/Hyperion, 2019)
Thirteen-year-old Nandu is selected to live in the newly established royal elephant breeding center near the Borderlands' jungle in Nepal, where he will raise the king's elephants. Rumors of poachers, threat of drought, wild rampaging herds, and tests from both man and nature threaten Nandu's world and throws him and Hira Prashad--the Center's bull elephant--into turmoil, but in that turmoil they will forge a bond of brotherhood.